New CNN-type ruthenium pincer NHC complexes. synthesis and catalytic activity. mild, efficient hydrogenation of esters - Fogler, Eran; Balaraman, Ekambaram; Ben-David, Yehoshoa; Leitus, Gregory; Shimon, Linda J. W.; Milstein, David (Organometallics, 2011)
New pincer ruthenium complexes (2–6) based on the new bipyridine-NHC ligand 1 were prepared and studied, resulting in an efficient catalytic hydrogenation of esters to the corresponding alcohols under mild conditions. Reaction of the ligand 1 with RuH(Cl)CO(PPh3)3, followed by reaction with one equivalent of the base KHMDS, gave the mixed phosphine-NHC complex 2, incorporating a C–H-activated bipyridine ligand. Complex 2 has an octahedral structure containing two phosphorus atoms trans to each other, a hydride trans to the NHC ligand, and CO trans to the C–H-activated carbon of the bipyridine ligand. Using the precursor complex Ru(p-cymene)Cl2(CO), reaction with 1 followed by treatment of the intermediate product with one equivalent of KHMDS resulted in formation of the dichloride pincer complexes 3a and 3b, which are in equilibrium, as indicated by variable-temperature 1H NMR. Complex 3a is an octahedral, neutral, and symmetric complex with the CO ligand positioned trans to the central pyridine group of the pincer ligand and the two chlorides trans to each other, as indicated by single-crystal X-ray diffraction. Complex 3b is cationic, with an outer-sphere chloride. Reaction of the NHC ligand 1 with LiHMDS at low temperature followed by addition of RuH(Cl)CO(PPh3)3 resulted in the mixed phosphine-NHC complex 4, which has an octahedral structure containing phosphorus trans to the hydride, a CO trans to the NHC ligand, and an outer-sphere chloride. Chloride substitution by BArF– gave the X-ray-characterized complex 5. Deprotonation of complex 4 with KHMDS resulted in formation of the dearomatized complex 6. The in situ prepared 6 (from complex 4 and an equivalent of base) is among the best catalysts known for the hydrogenation of nonactivated esters to the corresponding alcohols under mild conditions.

Synthesis of peptides and pyrazines from beta-aminoalcohols via extrusion of H2 catalyzed by ruthenium pincer complexes. ligand controlled selectivity - Gnanaprakasam, Boopathy; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Bitte wählen: Die Wahl des Katalysators, eines Ru-Pinzettenkomplexes, bestimmt, ob Peptide oder Pyrazine aus β-Aminoalkoholen entstehen: Der PNN-Komplex 1 führt, je nach Substituent R (siehe Schema), zu linearem Polyalanin oder zu cyclischen Dipeptiden, der PNP-Komplex 2 katalysiert die Bildung von Pyrazinen. Die Reaktionen finden in homogener Lösung unter neutralen Bedingungen statt.

Unprecedented catalytic hydrogenation of urea derivatives to amines and methanol - Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Angewandte Chemie, 2011)
Indirekte CO2-Hydrierung: Eine Hydrierung von Harnstoffen zu Aminen und Methanol (siehe Bild) wird durch einen RuII-Pinzettenkomplex mit dreizähnigem bipyridinbasiertem PNN-Liganden katalysiert und verläuft unter milden, neutralen Bedingungen bei einem H2-Druck von 13.6 atm. Da sich Harnstoffderivate ausgehend von CO2 erhalten lassen, ermöglicht dieser Ansatz die indirekte Hydrierung von Kohlendioxid zu Methanol.

Ruthenium pincer-catalyzed cross-dehydrogenative coupling of primary alcohols with secondary alcohols under neutral conditions - Srimani, Dipankar; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2012)
Cross-dehydrogenative coupling of primary alcohols with secondary alcohols to obtain mixed esters with the liberation of molecular hydrogen is achieved in high yield and good selectivity under neutral conditions, using a bipyridyl-based PNN ruthenium(II) pincer catalyst.

Use of ruthenium complexes for formation and/or hydrogenation of amides and related carboxylic acid derivatives - Milstein, David; Gunanathan, Chidambaram; Ben-David, Yehoshoa; Balaraman, Ekambaram; Gnanaprakasam, Boopathy; Zhang, Jing (US20120253042, US20160152663, 2012)
A process for preparing amides by reacting a primary amine and a primary alcohol in the presence of a Ruthenium complex to generate the amide and molecular hydrogen. Primary amines are directly acylated by equimolar amounts of alcohols to produce amides and molecular hydrogen (the only byproduct) in high yields and high turnover numbers. Also disclosed are processes for hydrogenation of amides to alcohols and amines; hydrogenation of organic carbonates to alcohols; hydrogenation of carbamates or urea derivatives to alcohols and amines; amidation of esters; acylation of alcohols using esters; coupling of alcohols with water and a base to form carboxylic acids; dehydrogenation of beta-amino alcohols to form pyrazines and cyclic dipeptides; and dehydrogenation of secondary alcohols to ketones. These reactions are catalyzed by a Ruthenium complex which is based on a dearomatized PNN-type ligand of formula A1 or precursors thereof of formulae A2 or A3.

Formation of tertiary amides and H2 by dehydrogenative coupling of primary alcohols with secondary amines catalyzed by ruthenium bipyridine-based pincer complexes - Srimani, Dipankar; Balaraman, Ekambaram; Hu, Peng; Ben-David, Yehoshoa; Milstein, David (Advanced Synthesis & Catalysis, 2013)
Dehydrogenative coupling of primary alcohols with secondary amines to form tertiary amides and dihydrogen (H2) is efficiently catalyzed by bipyridyl-based ruthenium pincer complexes (0.2–1 mol%) under neutral conditions (in case of the dearomatized complexes), or with added catalytic amount of base. The reaction is sensitive to steric hindrance; in the case of amidation of bulky secondary amines a less sterically hindered complex is more efficient. Selective acylation of primary amines in the presence of secondary amines was also demonstrated.

Stepwise metal-ligand cooperation via a reversible aromatization-deconjugation-sequence in ruthenium complexes with a tetradentate phenanthroline-based ligand - Langer, Robert; Fuchs, Ido; Vogt, Matthias; Balaraman, Ekambaram; Diskin-Posner, Yael; Shimon, Linda J. W.; Ben-David, Yehoshoa; Milstein, David (Chemistry - A European Journal, 2013)
The synthesis and reactivity of ruthenium complexes containing the tetradentate phenanthroline-based phosphine ligand 2,9-bis((di-tert-butylphosphino)methyl)-1,10-phenanthroline (PPhenP) is described. The hydrido chloro complex [RuHCl(PPhenP)] (2) undergoes facile dearomatization upon deprotonation of the benzylic position, to give [RuH(PPhenP-H)] (4). Addition of dihydrogen to 4 causes rearomatization of the phenanthroline moiety to trans-[Ru(H)2(PPhenP)] (5), followed by hydrogenation of an aromatic heterocycle in the ligand backbone, to give a new dearomatized and deconjugated complex [RuH(PPhenP*-H)] (6). These aromatization/deconjugation steps of the coordinated ligand were demonstrated to be reversible and operative in the dehydrogenation of primary alcohols without the need for a hydrogen acceptor. This aromatization/deconjugation sequence constitutes an unprecedented mode of a stepwise cooperation between the metal center and the coordinated ligand.

Synthesis, structures, and dearomatization by deprotonation of iron complexes featuring bipyridine-based PNN pincer ligands - Zell, Thomas; Langer, Robert; Iron, Mark A.; Konstantinovski, Leonid; Shimon, Linda J. W.; Diskin-Posner, Yael; Leitus, Gregory; Balaraman, Ekambaram; Ben-David, Yehoshoa; Milstein, David (Inorganic Chemistry, 2013)
The synthesis and characterization of new iron pincer complexes bearing bipyridine-based PNN ligands is reported. Three phosphine-substituted pincer ligands, namely, the known tBu-PNN (6-((di-tert-butylphosphino)methyl)-2,2′-bipyridine) and the two new iPr-PNN (6-((di-iso-propylphosphino)methyl)-2,2′-bipyridine) and Ph-PNN (6-((diphenylphosphino)methyl)-2,2′-bipyridine) ligands were synthesized and studied in ligation reactions with iron(II) chloride and bromide. These reactions lead to the formation of two types of complexes: mono-chelated neutral complexes of the type [(R-PNN)Fe(X)2] and bis-chelated dicationic complexes of the type [(R-PNN)2Fe]2+. The complexes [(R-PNN)Fe(X)2] (1: R = tBu, X = Cl, 2: R = tBu, X = Br, 3: R = iPr, X = Cl, and 4: R = iPr, X = Br) are readily prepared from reactions of FeX2 with the free R-PNN ligand in a 1:1 ratio. Magnetic susceptibility measurements show that these complexes have a high-spin ground state (S = 2) at room temperature. Employing a 2-fold or higher excess of iPr-PNN, diamagnetic hexacoordinated dicationic complexes of the type [(iPr-PNN)2Fe](X)2 (5: X = Cl, and 6: X = Br) are formed. The reactions of Ph-PNN with FeX2 in a 1:1 ratio lead to similar complexes of the type [(Ph-PNN)2Fe](FeX4) (7: X = Cl, and 8: X = Br). Single crystal X-ray studies of 1, 2, 4, 6, and 8 do not indicate electron transfer from the FeII centers to the neutral bipyridine unit based on the determined bond lengths. Density functional theory (DFT) calculations were performed to compare the relative energies of the mono- and bis-chelated complexes. The doubly deprotonated complexes [(R-PNN*)2Fe] (9: R = iPr, and 10: R = Ph) were synthesized by reactions of the dicationic complexes 6 and 8 with KOtBu. The dearomatized nature of the central pyridine of the pincer ligand was established by X-ray diffraction analysis of single crystals of 10. Reactivity studies show that 9 and 10 have a slightly different behavior in protonation reactions.